Metacognitive self regulation integrated with science technology society to improving problem solving ability in microbiology courses - Erlin, Euis; Rahmat, Adi; Purwianingsih, Widi (Universitas Negeri Jakarta, 2024)
The purpose of this study was to improve students’ problem-solving ability and metacognitive self-regulation (MSR) by applying science technology society (STS) learning model integrated with metacognitive self-regulation. The participants were 13 students from Department of Biology Education who took microbiology courses. A quasi-experimental method with one-group pre and posttest design was used in this study. Data were collected through pre and posttest with eight open ended questions to measure students’ problem-solving ability on four microbiology topics (food, pathogen, waste and water microbiology). These topics were studied sequentially in two months. The instrument used to measure MSR is a questionnaire with open-ended questions. This questionnaire was developed based on three aspects of MSR namely, planning, monitoring and evaluation. MSR questionnaire was administered to students at the end of each topic. The N-gain test was used to analyze the improvement of students' problem-solving ability on each topic. The average score of all aspects in MSR questionnaire was used to explore students’ metacognitive self-regulation. The correlation between MSR and problem-solving ability was analyzed using Pearson correlation. The results revealed that the N gain score of problem-solving ability was increased from 0.56 in the first topic to 0.7 in the next three topics. The average of MSR score also increased from 66.15 in the first topic to 87.23 in fourth topic. There was a positive correlation between students’ MSR and problem-solving ability. These results indicated that application of Science Technology Society integrated with MSR is an effective strategy in improving students’ problem-solving ability and MSR. The implementation of this research is to develop a lecture program as an effort to improve the learning process